Pengaruh Modal Usaha, Tenaga Kerja, Jumlah Pembeli Terhadap Pendapatan Pedagang di Pasar Krian, Kabupaten Sidoarjo Pada Tahun 2019 - Syahputra, Junico Dwi; Prayitno, Budi (Economie: Jurnal Ilmu Ekonomi, 2020)
The research final project discussed has the objective of knowing the impact of capital, labor, and the number of buyers on the income of traders in the krian market, Sidoarjo regency. This final project research uses quantitative methods. This final project research uses data obtained by means of final project research, interviews, and distributing questionnaires to grocery and food clothing traders in Krian market, Sidoarjo regency. The samples used were 80 groceries and food clothing traders. The analysis technique uses multiple linear regression analysis. The results of the final project research with a test of the regression coefficient with α = 5%, this shows that the variables of capital, labor, and the number of buyers have a positive impact on the income of groceries and food clothing traders in the Krian market, Sidoarjo regency.